Investigation action outlines and contribution of the workshop creativity developed by consultorio psicológico (Copsi) of Universidad Nacional Mayor de San Marcos - Oliveros M., Ricardo (2009)
It carries out a first evaluation of the Creativity Workshop of the Psychological office of the UNMSM, highlighting the present fortresses and the future potentialities of training in personal creativity practice, considering its contributions to the institutional development and to the community.